A phase II study of the pineal hormones melatonin and 5-methoxytryptamine plus cannabidiol in association with angiotensin 1-7 in the treatment of advanced solid tumour patients eligible for the only best supportive care - Lissoni, Paolo (2021)
Fil: Lissoni, Paolo. Instituto de Medicina Biológica; Italia